Mechanistic Insights into Copper-Catalyzed Azide–Alkyne Cycloaddition (CuAAC): Observation of Asymmetric Amplification - Osako, Takao; Uozumi, Yasuhiro (Synlett, 2015)
A mechanistic study of copper-catalyzed azide–alkyne cycloaddition (CuAAC) was examined using an enantioposition-selective asymmetric CuAAC as a probe reaction system. Based on the observed asymmetric amplification (a positive nonlinear effect), we proposed that a dimeric chiral copper complex is involved as a reactive intermediate in the copper-catalyzed azide–alkyne cycloaddition.
Keywords: asymmetric catalysis; azide–alkyne cycloaddition; Huisgen reaction; nonlinear effect